Determinantes sociais que envolvem as pessoas com doença falciforme: um estudo da contribuição do assistente social na atenção a estas pessoas - SANTOS, Zilda Cristina dos (2017)
Sickle cell disease (SCD) is the most common hereditary hematological disease in the world. It is characterized by a set of disorders that cause red blood cells to compromise oxygen transport. In Brazil, 3,500 children are born each year with SCD and 200,000 with sickle cell trait. The literature indicates that the social characteristics that involve this public are: majority of blacks, income less than a minimum salary, residence on the outskirts of cities and low schooling. These social determinants influence or aggravate the occurrence of health problems, condition the health-disease-care process and, therefore, have an important role in the health approach in its entirety. The objectives of this study were to evaluate the sociodemographic characteristics of people with SCD attended at the Clinical Hematology Clinic of the Federal University of TriânguloMineiro, as well as evaluate the recognition of people with SCD on the social determinants and their impact on the their daily life, and verify if the person with SCD recognizes the social worker's contribution to health and emphasizes the integral care of people with SCD. It is a qualitative research, so the focus and attention to the narratives of the participants, as well as the various forms of "expression" of their realities. Thirty people with SCD, residing in Uberaba - MG, aged over 18 years, in attendance at the Social Service of the HC / UFTM Hematology Clinic participated in the study. As a research instrument, a questionnaire with an elaborate script was used, which approached sociodemographic aspects, social determinants of health and social services in this scenario. To analyze the data, the thematic content analysiswas used, supported by the participant research. The female gender (18) and the high school level were predominant (15), followed by the elementary school (11). As for labor, housing, displacement and income, only four were formal workers, 12 unemployed; Seventeen lived in their own house, 22 depend on public transportation, and 16 had a family income of two to five minimum wages. The most cited daily difficulties were: staying at work and practicing sports (28). Seventeen knew some law, predominating Lei da Penha and Statute of the Child and Adolescent. The social determinants that involved these patients, such as family income, employment status, housing and transportation were similar to those found in the literature. The schooling was superior to that indicated by other Brazilian studies. All participants (30) acknowledge the contribution of the social worker. The study made clear the relevance of the social worker's work to this public, mainly evidenced by the improvement in access to social rights and benefits from the insertion of the social worker in the Clinic of Hematology of the HC-UFTM. Far from bringing definitive conclusions, the present study brought to light the "look" of the person with SCD about their daily reality, being inserted there, Social Service as a profession committed to the dignity of human life, thus committed to the citizen and their daily demands.